Numerical Simulation of Computer Virus Reaction-Diffusion Model using Cubic B-splines Collocation - Mittal, R.C.; Goel, Rohit; Ahlawat, N. (Discontinuity, Nonlinearity, and Complexity, 2026)
A reaction-diffusion model characterizing the dynamics of computer virus epidemic is considered in this paper. The propagation of viruses in computers is similar to the case of many infectious diseases so that the consideration of reaction-diffusion terms becomes necessary to look into the deep insights. The structure preserving analysis of virus propagation in the computers connected globally is performed through the extended reaction-diffusion mathematical model. A numerical scheme based on the collocation of cubic B-splines is proposed to investigate the computer virus epidemic model. The numerical results obtained are compared and validated by performing stability analysis and are found in good agreement with those already available in the literature. Due to the unavailability of the analytic solutions of these models, such a numerical simulation scheme can be of prime interest for biologists to interpret the results theoretically.